Risk Factors of Cervical Carcinoma and the Association of Age with Histopathological Diagnosis (The Planet, 2023)
Introduction: Within the high-risk group, HPV16 is themost oncogenic type, being responsible for approximately50% of all worldwide cervical cancers. This study aimed toanalyze the risk factors of cervical cancer and theassociation of age with histopathological diagnosis.Methods and materials: This cross-sectional study wascarried out in the Pathology department of Sir SalimullahMedical College and Mitford Hospital Dhaka, from July2017 to June 2019 with a total of 60 adult female patientswith cervical cancer diagnosed histopathologically.Results: The mean age of the patients having cervicalcancer was 57.75±8.96 years. 63.3% of patients belongedwere over 11 years of age and 60.0% of patients werepostmenopausal. The mean marital age was 16.48±2.22years. Most (81.7%) of the patients underwent ahysterectomy. 48.33% of the patients had moderately differentiated squamous cell carcinomaand 26.7% well differentiates squamous cell carcinoma. The average age of differenthistopathological entity was also found 60 years. However, when the age was compared withdifferent histopathological types of carcinoma (WHO-2014) it was found statisticallyinsignificant (p=0.714). Conclusion: This study concluded that late menarcheal age wasinversely associated with cervical cancer. Marriage at an early age, high parity, andirregular menstrual cycle are also important risk factors for cervical carcinoma. Menopausal status is a well-known risk factor for cervical cancer and most cases occur aftermenopause. Most of the tumor belongs to moderately differentiated and their age range were mostlybetween 50-59 years.
Keywords: scabies; pruritus; parasite; ivermectin